Electric field of the power terrestrial sources observed by microsatellite Chibis‐M in the Earth's ionosphere in frequency range 1–60 Hz. Issue 14 (17th July 2015) - Dudkin, Fedir; Korepanov, Valery; Dudkin, Denis; Pilipenko, Vyacheslav; Pronenko, Vira; Klimov, Stanislav
Abstract The power line emission (PLE) 50/60 Hz and the Schumann resonance (SR) harmonics were detected by the use of a compact electrical field sensor of length 0.42 m during microsatellite Chibis‐M mission in years 2012–2014. The initial orbit of Chibis‐M has altitude 500 km and inclination 52°. We present the space distribution of PLE and its connections with the possible overhead power lines. PLE has been recorded both in the shade and sunlit parts of the orbits as opposed to SR which have been recorded only in the nightside of the Earth. The cases of an extra long distance of PLE propagation in the Earth's ionosphere and increased value of SR Q factor have been also observed. These results should stimulate the ionosphere model refinement for ultralow frequency and extremely low frequency electromagnetic wave propagation as well as a study on new possibility of the ionosphere diagnostics.